Awareness and experiences of side effects and infections during chemotherapy treatment: a cross sectional survey among family caregivers of cancer patients in India - Roy, Sayan; M. G., Gopika; Vinoda Thulaseedharan, Jissa (International Journal Of Community Medicine And Public Health, 2023)
Background: Adequate understanding of side effects and infections is essential for family caregivers to ensure proper management for cancer patients during chemotherapy. The present paper describes the family caregivers' awareness of the symptoms of possible side effects and infections during chemotherapy treatment. Methods: Family caregivers were identified through the lodging facilities near the cancer treatment centres in Thiruvananthapuram and Mumbai. The cross-sectional survey was conducted using a structured interview schedule formulated in the Kobo-collect toolbox and analyzed using IBM-SPSS-Statistics-25. Results: Among the 217 family caregivers aged between 19 to 76 years, 83% were close relatives of the patients. The majority of the family caregivers were able to identify conditions such as hair loss (95%), appetite change (88%), and nausea/vomiting (88%) as side effects of chemotherapy. At the same time, participants recognized the symptoms of infections were less. Unusual vaginal discharge/irritation (57%) and burning/pain with urination (55%) were the commonly recognized symptoms of infections. From the list of symptoms, more than six out of the thirteen side effects and more than three out of seven infections were correctly identified by 82% and 42% of family caregivers, respectively. Conclusions: The family caregivers were largely aware of side effects but not much about infections. Since chemotherapy is an immune suppressive treatment, infection awareness among family caregivers is essential to avoid any serious complications during the treatment period. Communication with family caregivers on 'the symptoms and management' of 'side effects and infections' and when to seek treatment is crucial for cancer treatment success.